(3eQGJY GdZRdGf aj hUa GdMSGf ef GdZdeGfs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO ddg GdPj Ndb GdEfSGf aj CMSf Jbhje abO SCdfj dYV GdENhGf Cf CLeY dg ofHPI aj GdMSGf ef GdZdeGf s
(3BNQgG (B:s
(3bdJ(B: (3hdh bGd(B: (3dh de Jcf QhVI ddMSf Ch adcG eG cGf LeY ajc GdYUf hGdbeQ dcGf CHdZ aj GdeYfi Je eQGJY GdZRdGfhGdMeO ddg hMOg s
(3fSNI KGfjIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3JYGbH YdjgG fGSNGfs
(3hHChdgG bQGAI eDQNI SfI (B1192 (3g``` s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs